Pengaruh Harga, Desain Produk, Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Motor Matic Honda (Studi Pada Konsumen Dealer Putra Rinjani Tulungagung) - Barotut Taqiyah; Afi Rachmat Slamet; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to determine (1) the effect of price, product design, product quality and promotion on purchasing decisions of Honda automatic motorcycles at the Putra Rinjani Dealer Tulungagung, (2) the effect of price on purchasing decisions of Honda automatic motorcycles, (3) the influence of design product on purchasing decisions of Honda automatic motorcycles, (4) the effect of product quality on purchasing decisions of Honda automatic motorcycles, (5) the influence of promotion on Honda automatic motorcycle purchase decisions. This study uses a quantitative explanatory research method by distributing questionnaires to 145 respondents of Honda motorcycle consumers at the Putra Rinjani Dealer Tulungagung. The results showed that (1) the variables of price, product design, product quality and promotion simultaneously influence the purchase decision of Honda automatic motorcycles, (2) Price partially does not affect the purchase decisions of Honda automatic motorcycles, (3) Partial product design partial has no effect. . affect the purchasing decision of Honda matic motorcycles, (4) product quality has partial effect on purchasing decisions of Honda matic motorcycles, (5) promotion has partial effect on purchasing decisions of Honda matic motorcycles. Keywords: Price, Product Design, Product Quality, Promotion and Purchase Decision